Neuroprotective role of acamprosate and rasagiline in epilepsy: In silico and in vivo study - Kumar Sandeep; Singh Govind; Chhikara Manisha; Shukla Sunil; Khatri Ramchander; Dar Mohammad Ovais; Lather Amit; Hooda Tanuj (Scripta Medica)
Background/Aim: Current treatments for epilepsy have only indicative relief without smashing the pathological trademarks of the disease. The unmet need is to find new therapeutic active drug candidates for effective management of epilepsy and associated neurological disorders. The present study aimed to examine the antiepileptic agonistic potential of rasagiline and acamprosate in epileptic mice model. Methods: Docking studies were performed to predict the binding interaction of rasagiline and acamprosate towards N-methyl-D-aspartate (NMDA) glutamate receptors (PDB: 3QEL). The in vivo study was employed in Swiss albino mice. Acute epilepsy was induced by pentylenetetrazole (PTZ) and various behavioural and biochemical parameters were evaluated inconsistently with the pathophysiology of epilepsy. Results: All the behavioural and biochemical parameters were found to be improved with an increase in rasagiline dosage. The maximum dose of the rasagiline (4 mg/kg, po) produces the maximal anti-epileptic effects. When rasagiline at dose 4 mg/kg was co-administrated with acamprosate 400 mg/kg, the anti-epileptic potential was observed significantly higher than only rasagiline. Both compounds have good docking results with 3QEL in comparison with the PDB-binded ligand. Docking studies of rasagiline and acamprosate highlighted that these drugs have potential in the inhibition of NMDA receptor subunit GluN1 and GluN2B and in vivo studies showed their agonistic potential against epilepsy. Conclusion: The anti-epileptic potential of these drugs could be further explored using more specific anti-epileptic parameters. Further studies still required to be performed so as to explore its potential in clinical trials.